2019
DOI: 10.1111/1460-6984.12500
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of communication repair skills across three neurodevelopmental disabilities

Abstract: BackgroundThis study is a longitudinal follow‐up to prior work examining the important pragmatic skill of communication repair (i.e., the ability to respond effectively to a request for clarification of an unclear message) across three neurodevelopmental disabilities in which language skills are impaired: fragile X syndrome with and without autism spectrum disorder (FXS‐ASD; FXS‐O), idiopathic ASD (ASD‐O), Down syndrome (DS) and controls with typical development (TD). Prior work examining communication repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are several limitations of the current study that should inform future research. First, it is critical for future studies to examine whether the profiles identified here extend to females across these different neurodevelopmental conditions, given sex differences observed across clinical groups in previous studies (15,29,56,91,92). Sex-specific patterns are well documented in FXS, owing to females' second, unaffected X chromosome with normal FMR1-related protein expression and function.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
See 1 more Smart Citation
“…There are several limitations of the current study that should inform future research. First, it is critical for future studies to examine whether the profiles identified here extend to females across these different neurodevelopmental conditions, given sex differences observed across clinical groups in previous studies (15,29,56,91,92). Sex-specific patterns are well documented in FXS, owing to females' second, unaffected X chromosome with normal FMR1-related protein expression and function.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Participants were part of a longitudinal study of pragmatic language development in which assessments were completed approximately once per year for up to three time points. Some children had fewer time points due to a "rolling enrollment" structure of the study where participants who enrolled later did not have time for multiple yearly visits before the study ended, as described previously (56). The number of participants receiving each assessment at each time point is summarized in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…As in other areas, females with FXS frequently demonstrate less severe pragmatic impairment than males, although there is considerable variability (Abbeduto et al, 2008;Thurman et al, 2017a;Martin et al, 2020;Neal et al, 2022). Girls show deficits in signaling of non-comprehension as compared to TD peers matched on cognition, and there has been some research showing decreased responsivity in girls with FXS as they reach adolescence when asked to repair a communication breakdown (Thurman et al, 2017a;Martin et al, 2020).…”
Section: Related Factorsmentioning
confidence: 99%
“…As in other areas, females with FXS frequently demonstrate less severe pragmatic impairment than males, although there is considerable variability (Abbeduto et al, 2008;Thurman et al, 2017a;Martin et al, 2020;Neal et al, 2022). Girls show deficits in signaling of non-comprehension as compared to TD peers matched on cognition, and there has been some research showing decreased responsivity in girls with FXS as they reach adolescence when asked to repair a communication breakdown (Thurman et al, 2017a;Martin et al, 2020). Females with FXS who also meet criteria for ASD have been shown to be less likely to signal non-comprehension, initiate conversation, or make contingent remarks in conversation than those with FXS-O or individuals with DS and TD matched on nonverbal cognition.…”
Section: Related Factorsmentioning
confidence: 99%
“…Previous studies that have examined pragmatic language analysis using ELS have found that it distinguishes between various syndromes [8,10,[23][24][25]; however, some elements of pragmatic language have proven to be more challenging to characterize, including verbal self-repetition-also termed perseveration-which refers to the excessive self-repetition of a spoken word, phrase, sentence, or topic. Verbal self-repetition (hereafter, simply "repetitive language"), has been noted as prevalent in both ASD and FXS [26][27][28][29].…”
Section: Expressive Language Samplingmentioning
confidence: 99%